2007
DOI: 10.1021/ja067754j
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Chimeric Enzymes as Tools for Drug Discovery:  Generating Reliable Bacterial Screens for the Detection, Discovery, and Assessment of Estrogen Receptor Modulators

Abstract: Engineered protein-based sensors of ligand binding have emerged as attractive tools for the discovery of therapeutic compounds through simple screening systems. We have previously shown that engineered chimeric enzymes, which combine the ligand-binding domains of nuclear hormone receptors with a highly sensitive thymidylate synthase reporter, yield simple sensors that report the presence of hormone-like compounds through changes in bacterial growth. This work describes an optimized estrogen sensor in Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 66 publications
7
80
1
3
Order By: Relevance
“…To date, only a handful of bacterial HTS assays have been used to screen compound libraries against nonbacterial targets but each of these has successfully uncovered interesting lead molecules including estrogen receptor modulators, 42 HIV protease inhibitors 43,44 and, akin to our studies here, Ab42 aggregation inhibitors. 23 The use of bacteria for HTS studies is fast, inexpensive and reliable; however, one possible limitation is the potential difficulty of getting diverse compounds into cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only a handful of bacterial HTS assays have been used to screen compound libraries against nonbacterial targets but each of these has successfully uncovered interesting lead molecules including estrogen receptor modulators, 42 HIV protease inhibitors 43,44 and, akin to our studies here, Ab42 aggregation inhibitors. 23 The use of bacteria for HTS studies is fast, inexpensive and reliable; however, one possible limitation is the potential difficulty of getting diverse compounds into cells.…”
Section: Discussionmentioning
confidence: 99%
“…As evidence that permeability is not necessarily a limiting factor, other groups have used E. coli-based screening assays to isolate lead compounds from structurally diverse libraries. [42][43][44] Along similar lines, Hecht and coworkers successfully employed wt E. coli cells expressing an Ab42-GFP reporter to isolate an aggregation inhibitor from a library of triazine derivatives that was nearly identical to the library screened here. 23 It should be noted that their hit compound E2 was also a positive hit in our study, although at the lower screening doses used here it was not as effective as the four inhibitors that we characterized here.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the activity of the thymidylate synthase reporter is modulated by hormone binding to the LBD, allowing the production of E. coli cell lines that report the presence of hormone-like ligands through a simple growth phenotype assay (69). Initial studies used the human estrogen (ER␣) and thyroid hormone (TR␤-1) receptors and showed that this sensor can differentiate between receptor agonists and antagonists (71). Further, the modular design of the sensor has simplified the development of additional biosensors based on estrogen (ER␣ and ER␤) (69) and thyroid hormone (TR␣-1 and TR␤-1) receptors (72), as well as the human peroxisome proliferator-activated receptor ␥ (PPAR␥) receptor (73) and several animal estrogen receptors (74).…”
Section: Detecting Small Moleculesmentioning
confidence: 99%
“…This is reflected in higher EC 50 values when compared with values obtained in conventional transcriptional assays and in vitro binding assays. There are several possible reasons for these disparities, including differences in ligand transport into the cells and the non-transcriptional nature of the assay (Skretas et al 2007). For example, the bacterial assay relies on free diffusion or nonspecific transport of the ligands though the cell membrane, which will be differentially affected by the physical properties of each ligand.…”
Section: Discussionmentioning
confidence: 99%